(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
The provision of effective technical support is essential to optimize the safe operation of nuclear power plants (NPPs) and to maximize their availability and productivity. Renewed interest in new reactor build pro grams, not only in countries with already established nuclear programs but also in many other countries with limited or no work force expe rienced in the design, licensing, construction and operation of nuclear power plants, has resulted in a need for technical, scientific and support organizations (TSOs) to support regulatory bodies in carrying out their mandated responsibilities.